Gladys Black letter to Nicholas S. Halmi regarding winter bird sightings, February 9, 1979 - Black, Gladyset al (1979)
Letter from Gladys Black to Nicholas S. Halmi providing additional statewide bird sightings, February 9, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed